Misogynistic Interpretations of Hadith:: A Foucauldian Genealogical Analysis - Siti Masykuroh; Masruchin Masruchin (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Universitas Islam Negeri Madura, 2026)
This study examines misogynistic narratives in the hadith tradition by investigating how specific hadiths concerning women have been constructed and legitimized as dominant discourses within Muslim societies. The analysis focuses on hadiths portraying women as sources of temptation (fitnah), deficient in intellect and religion, unqualified for leadership, restricted in their mobility, and created from a crooked rib. The study employs Asma Barlas's critical hermeneutics as a supporting interpretive approach to distinguish between the hadith text, its socio-historical context, and its interpretive tradition, thereby identifying patriarchal assumptions embedded in their reception and interpretation. Michel Foucault's genealogical approach serves as the primary analytical framework to trace the historical processes through which these interpretations were produced, codified, legitimized, and reproduced within relations of power. The findings demonstrate that misogynistic tendencies are not inherent in the hadith texts themselves but are products of interpretive constructions shaped by patriarchal socio-historical contexts. Genealogical analysis further reveals that these interpretations were institutionalized through hadith commentaries, Islamic jurisprudence, and religious institutions, eventually evolving into a regime of truth that positioned women in subordinate social and religious roles. This study argues that the critique should be directed not at the authority of hadith as a source of Islamic teaching, but at the historical processes through which patriarchal interpretations have been produced and sustained.